DOUBLE STAGE SHRINKAGE BAYES ESTIMATOR FORTHE VARIANCE OF NORMAL DISTRIBUTION WHEN THEMEAN IS UNKNOWN BY USE THE SHRINKAGE FUNCTIONWEIGHTED OF FIRST SAMPLE SIZE . - Al-Bermani, Mohammad (Iraqi Journal of Science, 2024)
In this articale we depend on Shrinkage function of Bayesian estimator for thevariance of normal distribution when the mean is unknown weighted by Shrinkagefactor like afunction of first sample size to obtain the double stage ShrinkageBayesian estimator for the variance when using include double stage Shrinkageestimator formula.